Inhibition of xanthine oxidase improves myocardial contractility in patients with ischemic cardiomyopathy - Baldus, Stephan (2006)
Reactive oxygen species, in particular superoxide, have been closely linked to the underlying pathophysiology of ischemic cardiomyopathy: superoxide not only mediates mechanoenergetic uncoupling of the myocyte but also adversely impacts on myocardial perfusion by depleting endothelial-derived nitric oxide bioavailability. Xanthine oxidase generates superoxide upon oxidation of hypoxanthine and xanthine and has been detected in cardiac myocytes and coronary endothelial cells of patients with ischemic heart disease. Here we investigated the effects of oxypurinol, a xanthine oxidase inhibitor, on myocardial contractility in patients with ischemic cardiomyopathy. Twenty patients (19 males, 66±8 years) with stable coronary disease, severely suppressed systolic function (left ventricular ejection fraction 22±2%), and nonelevated uric acid plasma levels received a single intravenous dose of oxypurinol (400 mg). Cardiac MRI studies, performed before and 5.2±0.9 h after oxypurinol administration, revealed a reduction in end-systolic volumes (−9.7±4.2%; p=0.03) and an increase in left ventricular ejection fraction (+17.5±5.2%; p=0.003), whereas 6 patients (6 males, 63±3.8 years, ejection fraction 26±5%) who received vehicle only did not show significant changes in any of the parameters studied. Oxypurinol improves left ventricular function in patients with ischemic cardiomyopathy. These results underscore the significance of reactive oxygen species as important pathophysiological mediators in ischemic heart failure and point toward xanthine oxidase as an important source of reactive species that serve to modulate the myocardial redox state in this disease.